2019
DOI: 10.3389/fmicb.2019.02860
|View full text |Cite
|
Sign up to set email alerts
|

GLAPD: Whole Genome Based LAMP Primer Design for a Set of Target Genomes

Abstract: Loop-mediated isothermal amplification (LAMP) technology has been applied in a wide range of fields such as detection of foodborne bacteria and clinical pathogens due to its simplicity and efficiency. However, existing LAMP primer designing systems require a conserved gene or a short genome region as input, and they can't design group-specific primers. With the growing number of whole genomes available, it is possible to design better primers to target a set of genomes with high specificity based on whole geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 38 publications
0
25
0
1
Order By: Relevance
“…Another potential inherent advantage is the ability to multiplex gene targets allowing the detection of multiple respiratory pathogens [ 18 ] such as SARS-CoV-2, influenza and respiratory syncytial virus (RSV). It is not known what the upper limit of multiplexing of LAMP primers is, and they are considerably more complex to design than PCR primers [ 19 ]. Given the advantages of LAMP in terms of speed of amplification [ 8 ] and sensitivity of detection, an exploration of LAMP multiplexing is urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential inherent advantage is the ability to multiplex gene targets allowing the detection of multiple respiratory pathogens [ 18 ] such as SARS-CoV-2, influenza and respiratory syncytial virus (RSV). It is not known what the upper limit of multiplexing of LAMP primers is, and they are considerably more complex to design than PCR primers [ 19 ]. Given the advantages of LAMP in terms of speed of amplification [ 8 ] and sensitivity of detection, an exploration of LAMP multiplexing is urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…LAMP relies on 6 different primers, suggesting a higher degree of specificity than conventional PCR and qPCR using two primers [ 17 , 18 ]. This makes LAMP assay not only susceptible to the formation of primer dimers, but also cross contamination by aerosol leading to false-positive results much easier than conventional PCR and qPCR [ 19 , 32 , 33 , 34 ]. Indeed, in this study, we have observed some qPCR negative samples (< 100 fg/μL) with C T values between 35 to 40, which triggered color changes that were caused by non-specific amplification products (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential inherent advantage is the ability to multiplex gene targets allowing the detection of multiple respiratory pathogens (16) such as SARS-CoV-2, influenza and respiratory syncytial virus (RSV). It is not known what the upper limit of multiplexing of LAMP primers is, and they are considerably more complex to design than PCR primers (17). Given the advantages of LAMP in terms of speed of amplification (9) and sensitivity of detection, an exploration of LAMP multiplexing is urgently required.…”
Section: Discussionmentioning
confidence: 99%